Profile of John Hopfield and Geoffrey Hinton: 2024 Nobel laureates in Physics - James L. McClelland (Proceedings of the National Academy of Sciences, 2025)
The 2024 Nobel Prize in Physics recognizes breakthroughs contributing to the emergence of a new understanding of the computations that underlie human intelligence, with profound implications for artificially intelligent systems. John Hopfield and Geoffrey Hinton played seminal roles in these breakthroughs. I begin by characterizing the scientific context in which the new understanding of intelligence began to arise. I then consider Hopfield’s and Hinton’s ideas and their centrality in the sciences of natural and artificial intelligence, while mentioning others who made major contributions. I conclude with a brief consideration of the current state of the fields these ideas have influenced and of the importance of governmental and scientific organizations in the past and future of these sciences.